MEASUREMENT AND DISCLOSURE OF CREDIT RISK MANAGEMENT IN THE LIGHT OF THE FINANCIAL REPORTING STANDARD IFRS 9 AN APPLIED STUDY IN A SAMPLE OF IRAQI PRIVATE BANKS - Muthanna Abed Kadhim; Laith Jawad Kadhim (Scholar Express Journals, 2023)
This study aimed to clarify the role of the application of the International Financial Reporting Standard (IFRS:9) in credit risk management, by applying to Iraqi private banks. The study population is represented by all Iraqi private banks, which number (25) private commercial banks, and an arbitrary sample has been selected from these banks represented in that the financial statements and the clarifications complementing the bank are complete and issued quarterly and apply international standards and standard (IFRS:9) in accordance with the instructions The Central Bank of Iraq and thus the study sample becomes (5) banks, after excluding the banks that are not registered in the Iraqi Stock Exchange, and Islamic banks, which have recorded (30) views, and the financial data was obtained from the published financial reports for the period from (2016-2021) In the Iraq Stock Exchange and among the banks surveyed, it was used in the analysis of financial data (program, Excel 2010, SPSS, and Eviews 11 program) .
Keywords: International Financial Reporting Standard; Credit risk management; Iraqi private banks